Making Print Tool Gambir Sap Parallel Slinder System - Jasman, Jasman; Erizon, Nelvi; Irzal, Irzal; Ardi, Junil (Teknomekanik, 2019)
The problems that exist in the former group are the process of knowing the results of processing gambir sap is still done manually. To print 20 kg of gambier sap, it takes about 5 to 8 hours. Through this service activity, the team wanted to overcome the problem by providing a sap gambir. The purpose of implementing this service activity is to provide a solution to the problems faced by gambier farmers in the process of printing sap gambir. The method of applying science and technology carried out in this activity is to provide introductory theories, demonstrations, and practices. The introductory theory is applicable, namely the introduction of tools, how to use them, their functions and application applications in the field. The realization of the service to the community of Kenagarian Lampanjang Sutera Pesisir Selatan Subdistrict was held on October 6, 2018. The tool that was handed over to the community of Kenagarian Lampanjang Kecamatan Sutera was a unit of a parallel cylinder printer. Application of appropriate technology that is applied to processing gambir leaves must be adjusted to the productivity of printed sap gambir. The amount of gambir sap obtained by gambir farmers will adjust the capacity of the gambir sap. The tool devoted to the community has cylindrical media made with wood media with a thickness of 70 m. The mould cylinder will print the sap of gambir according to the size sold on the market and have a gum pushing media from the mould which serves to release the sap that is in the cylinder mould. This driving media is also made using wood.